Analisis Kesuksesan Rail Document System (RDS) Pada Pegawai PT.KAI DAOP 8 Surabaya Dengan Menggunakan Metode Delone dan McLean - Ardiansah, Achmad Setiawan; Sunarto, Dewiyani; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Rail Document System (RDS) PT. Kereta Api Indonesia is an application media that can be used for all employees that will do correspondence process. This application is made with expectation for helping the smooth of the correspondence process in PT. KAI Daerah Operasional Surabaya (Dan op 8). It make the developer wants to know the succession and the any variables that influence the succession of RDS for PT. KAI’s employees. The solution of the problem is doing the RDS’s succession variables analysis in PT. KAI Daop 8 by using Delone and Mclean methods.     The purpose of this study is for knowing the succession and the variables that more influence in the use of RDS by using Structured Equation Model (SEM) Partial Last Square (PLS). Taking sample is using Stratified Random Sampling (SRS) method in PT. KAI’s employees and the determination of sample number by using slovin formula.      Based on the results of the analysis on the Delone and McLean models of 68 respondents it can be seen the variables that affect the success of RDS: net benefits are influenced by the use and satisfaction of users, while the use is influenced by the quality of information and service quality. For user satisfaction is not affected by the independent variables of system quality, information quality and service quality. The quality of the system itself does not affect the dependent variable that is the use, the satisfaction of the use and the net benefits.Analisis Kesuksesan Rail Document System (RDS) Pada Pegawai PT.KAI DAOP 8 Surabaya Dengan Menggunakan Metode Delone dan McLean